The hemorrhagic syndrome of leptospirosis: an experimental study in guinea pigs - João José Pereira da Silva; Bernardino Alves de Souza Netto; Walter Lilembaum; Maria Erbene Amorim Melo Alvim; Albanita Viana de Oliveira (Revista da Sociedade Brasileira de Medicina Tropical, 1995)
The hemorrhagic syndrome of leptospirosis was studied in guinea pigs. The study correlates hematological, histopathological and immunohistochemical alterations in sixty animals inoculated by the intraperitoneal route with lml of the culture of virulent strain of Leptospira interrogans serovar copenhageni. Leptospirae antigens were detected by immunoperoxidase, chiefly in liver, kidney and heart muscle capillaries. Possible pathogenic mechanisms responsible for hemorrhagic syndrome are discussed with emphasis on toxic and anoxic attacks causing damage to endothelia, platelet depletion and alterations to hemostasia rates: prothrombin time [FT], partial thromboplastin time [PIT] and fibrinogen concentrations. Tide clinical-laboratoiy picture is compatible with the histopathological observation of disseminated intravascular coagulation [D1C] in most of the guinea pigs from day 4 of infection.